2021
DOI: 10.1039/d0nj05437b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mechanical and thermal performance of multiwalled carbon nanotubes-filled polypropylene/natural rubber thermoplastic elastomers

Abstract: Effect of multiwalled carbon nanotubes (MWCNT) on mechanical, dynamic mechanical and thermal properties of the polypropylene/natural rubber (PP/NR) blends having two different blend composition were studied. The observations were correlated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…The wide application of PLA is limited by its low crystallization degree/rate, high brittleness and low thermal resistance (its thermal resistance is limited by its low glass transition (60 • C) [98]). The thermal properties of natural fiber reinforced thermoplastic composites were studied by numerous researchers [41,[99][100][101][102][103][104][105][106].…”
Section: Type Of Matrixmentioning
confidence: 99%
See 2 more Smart Citations
“…The wide application of PLA is limited by its low crystallization degree/rate, high brittleness and low thermal resistance (its thermal resistance is limited by its low glass transition (60 • C) [98]). The thermal properties of natural fiber reinforced thermoplastic composites were studied by numerous researchers [41,[99][100][101][102][103][104][105][106].…”
Section: Type Of Matrixmentioning
confidence: 99%
“…Table 2 summarizes several studies which present the stages of decomposition of different natural fiber reinforced composites. 290-380 • C: the cellulose and lignin degradation [149] Several authors used the thermogravimetric analysis to determine the thermal properties of natural fiber composites [52,53,84,85,104,107,128,[150][151][152]. For example, Boopalan et al [153] studied the thermal properties of jute (J)/banana (B) reinforced epoxy composites.…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 99%
See 1 more Smart Citation
“…As filler agglomerates tend to form at higher MWCNTs loading, hindering the uniform distribution of stress from filler to the polymer phase to some extent, MWCNTs is not imparting further strengthening or reinforcement effect beyond 9 phr. [ 29 ] The pure rubber blend shows the elongation break of 733.87 ± 10.57. Upon introduction of 3 phr MWCNTs, the elongation break increases to 783.24 ± 13.09 and it remains a similar value until the MWCNTs loading beyond 9 phr.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, several factors such as the dispersion state of the nanofiller, the blend morphology induced by nanofiller, the interaction between the blend and filler components and the selective localization of nanofillers at the blend interface can modify the properties of immiscible blend nanocomposite. 28 For example, the addition of CNT showed the occurrence of interfacial adhesion with rPET phase and thus promoted an offset effect on the reaction of rPET and a decrement in the rigidity of the molecular chain in the rPET/thermoplastic polyurethane composites. 29 In another study of hybrid CNT/clay nanofillers on immiscible PE/PP blend, the finding reported the selective localization of CNT within the PE phase, while the clay particles showed affinity towards the PP phase, however due to the poor adhesion between PP matrix and the clay, the mechanical properties were degraded.…”
Section: Introductionmentioning
confidence: 99%